The curriculum and pupils' responses : a case study in an open secondary school in South Africa - Cohen, Susan (My University, 1995)
In the mid 1970s certain hitherto white private schools began admitting pupils of other race groups. As desegregated schools become more common in this country, there is need for curriculum research that can inform both policy makers and practioners. This study explores curriculum issues at a secondary school ten years after it admitted pupils of all race groups. Located within the qualitative research paradigm, this research is an ethnographic case study based on a year's participant observation in the school The study focused on teachers' approaches to their work, their aims, choice of material and methodology, academic achievement patterns, perceptions of factors influencing these and strategies for dealing with them; pupils' responses to different curriculum content, teaching styles and strategies, and the interplay between social interaction and learning. Within a framework of Similarity, there were differences among black and white pupils' expectations of the school, their evaluation of subjects, their prioritization of constructs of good teaching and their evaluation of the school in fulfilling key expectations. Black pupils underachieved academically. and were relatively more sensitive to the subtle tension underlying race group interaction. The curriculum was perceived as basically assimilationist, and most teaching conservative. geared toward narrow academic aims. A small group of teachers who promoted a less Eurocentric approach which tended to be more pupil-centered, activity-based and issue-centered met some opposition from their colleagues. The study highlights the interplay between social interaction and achievement, the need to address both social and personal educational aims together with academic achievement. The findings suggest that unless certain key curriculum changes are implemented, black pupils are likely to remain academically marginalized in open schools, and desegregated schools run the risk of contributing little to social change.
A Dissertation Submitted to the Faculty of Education University of the Witwatersrand, Johannesburg for the Degree of Doctor of Philosophy
Keywords: School integration -- South Africa.; Multicultural education -- South Africa.; Education, Secondary -- South Africa.; High school students -- South Africa.; Curriculum planning -- South Africa